Empowering PKK Mothers in Klagensrampat Village: Accelerating income through ASMAN TOGA management - Fajri, Mega Barokatul; Bait, Jennifer Farihatul; Pratiwi, Elasari Dwi (Universitas Muhammadiyah Magelang, 2025)
The purpose of this community service is to empower PKK mothers in Klagensrampat Village, Maduran District, Lamongan Regency, through the